Capturing the financial cycle in Europe - Hanno Stremmel (European Central Bank (ECB), 2015)
In this study, we approximate the financial cycle in Europe by combining potential common and relevant financial indicators. We consider different credit aggregates and asset prices but also incorporate banking sector indicators for 11 European countries. We develop seven different synthetic financial cycle measures in order to best capture the characteristics of the financial cycle. We assess the various financial cycle measures using both graphical and statistical investigation techniques. The best fitted financial cycle measure includes the following financial ingredients: credit to GDP ratio, credit growth and house prices to income ratio. This study also highlights potential applications for the financial cycle measure in the macro-prudential policy context.
Keywords: E30; E44; E61; G18; G28; 330; financial crises; financial cycle; financial regulation; medium-term